Customer Understanding of Fiat Money in BSI’s Hajj Savings with Mudharabah Contract in West Aceh - Fitriana; Muliza; Hendrawan, Yoni (LPPM ISNJ Bengkalis, 2026)
Purpose - This study aims to examine the level of customer understanding of the use of fiat money in BSI Hajj savings with mudharabah contracts. Methods - The method used is quantitative with data analysis using univariate analysis. The results of the study indicate that Hajj savings customers in West Aceh have a good understanding regarding the use of fiat currency in Hajj savings using mudharabah contracts at BSI in West Aceh. Findings - The level of customer understanding of the use of fiat money in Hajj savings using mudharabah contracts at BSI in West Aceh is that those with elementary/secondary education are 3.9 and those with higher education are 4.00, this difference is very small (0.1/2.5%), this is in accordance with the results of the t-test which shows a sig. (2-tail) value of 0.122 > 0.05. The results of the t-test explain that there is no significant difference in the understanding of customers with low/medium education and customers with higher education. Implications - This study provides implications that the knowledge of Hajj savings customers about the legal status of the use of fiat money is very important for the perfection of the Hajj pilgrimage.